(untitled) (Eurasian Medical Research Periodical, 2024)
Biological complications affecting implant osseointegration are of great interest in modern dentistry. Such complications mainly refer to inflammatory conditions associated with bacterial contamination. Two clinical varieties can be distinguished: mucositis and peri-implantitis. Although the presence of an inflammatory lesion is a common feature of both conditions, only the latter form is manifested by loss of supporting bone. Mucositis is thought to precede peri-implantitis. Over the past two decades, the use of dental implants has become a common treatment to replace missing teeth